The following integrals look like they might have a closed form, but Mathematica could not find one. Can they be calculated, perhaps by differentiating under the integral sign?

$$I_1 = \int_{-\infty }^{\infty } \frac{\sin (x)}{x \cosh (x)} \, dx$$ $$I_2 = \int_{-\infty }^{\infty } \frac{\sin ^2(x)}{x \sinh (x)} \, dx$$


5 Answers 5


First I'm going to evaluate $$\int_{-\infty}^{\infty} \frac{\cos ax}{\cosh x} \ dx .$$

Integrate the function $ \displaystyle f(z) = \frac{e^{iaz}}{\cosh z}$ around a rectangle on the complex plane with vertices at $z= R$, $ z= R + i \pi$, $z= -R + i \pi$, and $z= - R$.

As $R \to \infty$, $ \displaystyle \int f(z) \ dz$ vanishes on the left and right sides of the rectangle.

So going around the rectangle counterclockwise, we get

$$ \int_{-\infty}^{\infty} f(x) \ dx + \int_{\infty}^{-\infty} f(t + i \pi) \ dt = 2 \pi i \ \text{Res} [f(z),i \pi] ,$$

which implies

$$ (1+ e^{- a \pi}) \int_{-\infty}^{\infty} \frac{e^{iax}}{\cosh x} \ dx = 2 \pi i \lim_{z \to i \pi /2} \frac{e^{iaz}}{\sinh z} = 2 \pi \ e^{- a \pi /2} .$$

And equating the real parts on both sides of the equation, we get

$$ \int_{-\infty}^{\infty} \frac{\cos ax}{\cosh x} \ dx = \frac{2 \pi}{e^{a \pi /2} + e^{- a \pi/2}} = \pi \ \text{sech} \left( \frac{a \pi}{2}\right) .$$


$$ \begin{align} \int_{0}^{a} \int_{-\infty}^{\infty} \frac{\cos ax}{\cosh x} \ dx \ da &= \int_{-\infty}^{\infty} \int_{0}^{a} \frac{\cos ax}{\cosh x} \ da \ dx \\ &= \int_{-\infty}^{\infty} \frac{\sin ax}{x \cosh x} \ dx \\ &= \pi \int_{0}^{a} \text{sech} \left(\frac{a \pi}{2} \right) \ da \\ &= 2 \int_{0}^{a \pi /2} \text{sech}(u) \ du \\ &= 4 \int_{0}^{a \pi /2} \frac{e^{u}}{1+e^{2u}} \ du \\ &= 4 \int_{1}^{e^{a \pi /2}} \frac{1}{1+w^{2}} \ dw \\ &= 4 \left(\arctan (e^{a \pi /2}) - \frac{\pi}{4} \right) . \end{align}$$


$$ \int_{-\infty}^{\infty} \frac{\sin x}{x \cosh x} \ dx = 4 \arctan (e^{\pi /2}) - \pi \approx 2.3217507819 . $$

  • $\begingroup$ I accepted this answer because it gives a slightly easier derivation, but Graham's method is very nice as well. $\endgroup$
    – user111187
    May 22, 2014 at 12:32
  • $\begingroup$ @user111187 Thanks. $\endgroup$ May 22, 2014 at 12:38
  • $\begingroup$ I concur, quite elegant. $\endgroup$ May 22, 2014 at 12:42
  • $\begingroup$ But isn't $$\frac2{e^{a\pi/2}-e^{-a\pi/2}}=\text{csch}\left(\frac{a\pi}2\right)$$? $\endgroup$ Mar 20, 2016 at 2:11
  • $\begingroup$ @user5713492 Thanks for spotting that. There were 2 typos. $\endgroup$ Mar 20, 2016 at 5:06

For the first one we need: $$\int _{-1/2}^{1/2}\!{{\rm e}^{2\,iax}}{da}={\frac {\sin \left( x \right) }{x}}\tag{1}$$ $$ \frac{1}{\cosh \left( x \right)}=-2\,\sum _{n=1}^{\infty } \left( -1 \right) ^{n}{{\rm e}^{- \left| x \right| \left( 2\,n-1 \right) }}\tag{2}$$ $$\int _{-\infty }^{\infty }\!{{\rm e}^{2\,iax}}{{\rm e}^{- \left| x \right| \left( 2\,n-1 \right) }}{dx}=- \frac{1}{\left( 2\,ia-2\,n+1 \right) }- \frac{1}{\left( -2\,ia-2\,n+1 \right)}\tag{3}$$ $$-2\,\sum _{n=1}^{\infty } \left( -1 \right) ^{n} \left(- \frac{1}{\left( 2\,ia-2\,n+1 \right) }- \frac{1}{\left( -2\,ia-2\,n+1 \right)} \right) ={ \frac {\pi }{\cosh \left( \pi \,a \right) }}\tag{4}$$ we get:

$$ \begin{aligned} \int _{-\infty }^{\infty }\!{\frac {\sin \left( x \right) }{x\cosh \left( x \right) }}{dx}&=\int _{-1/2}^{1/2}\!{\frac {\pi }{\cosh \left( \pi \,a \right) }}{da}\\ &=2\,\arctan \left( { {\rm e}^{1/2\,\pi }} \right)-2\,\arctan \left( {{\rm e}^{-1/2\,\pi }} \right)\\ &=2\,\arctan \left( \sinh \left( \frac{1}{2}\,\pi \right) \right) \end{aligned}\tag{5}$$ where the last part follows from $(2)$ and the Taylor series for arctan: $$\arctan \left( x \right) =\sum _{n=0}^{\infty }{\frac { \left( -1 \right) ^{n}{x}^{2\,n+1}}{2\,n+1}}\tag{6}$$

For the second one we need: $$ \frac{1}{\sinh \left( x \right) }=2\,\sum _{n=1}^{\infty } {{\rm e}^{-x \left( 2\,n-1 \right) }}\tag{7}$$ $${\frac { \sin^2 \left( x \right)}{x}}=-\frac{1}{2}\,\sum _{ m=1}^{\infty }{\frac { \left( -1 \right) ^{m}{2}^{2\,m}{x}^{2\,m-1}}{ \left( 2\,m \right) !}}\tag{8}$$ $$\int _{0}^{\infty }\!{x}^{2\,m-1}{{\rm e}^{-x \left( 2\,n-1 \right) }} {dx}={\frac { \left( 2\,m-1 \right) !}{ \left( 2\,n-1 \right) ^{2\,m}} }\tag{9}$$ $$\cot \left( z \right) -\frac{1}{z}=-\frac{2}{\pi}\,\sum _{m=1}^{\infty }\zeta \left( 2\,m \right) \left( {\frac {z}{\pi }} \right) ^{2\,m-1}\tag{10}$$ From $(6,7,8)$: $$ \begin{aligned} \int _{0}^{\infty }\!{\frac { \sin^2 \left( x \right)}{x\sinh \left( x \right) }}{dx}&=-\frac{1}{2}\,\sum _{m=1}^{\infty } \left( \frac{\left( -4 \right) ^{m}}{m}\sum _{n=1}^{\infty }{\frac {1}{\left( 2\,n-1 \right) ^{2\,m}}} \right)\\ &=\frac{1}{4}\sum _{m=1}^{\infty }\,{\frac {\zeta \left( 2\,m \right) \left( {4}^{m}-1 \right) \left( -1 \right) ^{m}}{m}} \end{aligned}\tag{11}$$ and after integrating $(10)$ once we know that: $$\ln \left( {\frac {\sin \left( z \right) }{z}} \right) =-\sum _{m=1}^ {\infty }\frac{\zeta \left( 2\,m \right)}{m} \left( {\frac {z}{\pi }} \right) ^{2\,m}\tag{12} $$ so by comparing $(11)$ with $(12)$ we know that: $$ \begin{aligned}\int _{0}^{\infty }\!{\frac { \sin^2 \left( x \right) }{x\sinh \left( x \right) }}{dx}&=\frac{1}{2}\,\ln\!\left( \frac{1}{2}\,{\frac {\sinh \left( 2\,\pi \right) }{\sinh \left( \pi \right) }} \right)\\ &=\frac{1}{2}\,\ln \left( \cosh \left( \pi \right) \right) \end{aligned}$$

  • $\begingroup$ I thought maybe my answer was wrong. But it seems to be numerically the same. Nice answer, BTW. +1 $\endgroup$ May 21, 2014 at 21:02
  • $\begingroup$ Yeah I get your answer if I use symmetry in the final integration to integrate over $+a$ only. Yours is nice too +1 :) $\endgroup$ May 21, 2014 at 21:06
  • 1
    $\begingroup$ Nice evaluation of the second integral as well. $\endgroup$ May 21, 2014 at 22:55

For $I_2$, we can use a well-known result: $$ \int_{-\infty }^{\infty } \frac{\sinh (ax)}{\sinh(bx)}dx=\frac{\pi}{b}\tan\frac{a\pi}{2b}. $$ Note $\sinh(ix)=\sin(x), \tanh(ix)=\tan(x)$. Thus $$ \int_{-\infty }^{\infty } \frac{\sin (ax)}{\sinh(bx)}dx=\int_{-\infty }^{\infty } \frac{\sinh (iax)}{\sinh(bx)}dx=\frac{\pi}{b}\tanh\frac{a\pi}{2b}. $$ For $I_2$, define $$ I_2(a)=\int_{-\infty }^{\infty } \frac{\sin^2(ax)}{x\sinh (x)}dx. $$ Then $I_2(0)=0$ and $I_2(1)=I_2$. Now \begin{eqnarray} I_2'(a)&=&\int_{-\infty }^{\infty } \frac{2\sin(ax)\cos(ax)}{\sinh (x)}dx\\ &=&\int_{-\infty }^{\infty } \frac{\sin(2ax)}{\sinh (x)}dx\\ &=&\pi\tanh(a\pi). \end{eqnarray} So $$ I_2(1)=\int_0^1\pi\tan(a\pi)da=\ln(\cosh(a\pi)). $$


$\newcommand{\+}{^{\dagger}} \newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\down}{\downarrow} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\isdiv}{\,\left.\right\vert\,} \newcommand{\ket}[1]{\left\vert #1\right\rangle} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert} \newcommand{\wt}[1]{\widetilde{#1}}$

  1. $\ds{\large\color{#000}{\tt I_{1}\equiv \int_{-\infty }^{\infty }{\sin\pars{x} \over x\cosh\pars{x}} \,\dd x}}$
    \begin{align}I_{1}&\equiv\color{#c00000}{ \int_{-\infty }^{\infty }{\sin\pars{x} \over x\cosh\pars{x}} \,\dd x} =\int_{-\infty }^{\infty } {2\expo{x} \over \expo{2x} + 1}\int_{0}^{1}\cos\pars{kx}\,\dd k\,\dd x \\[3mm]&=2\Re\int_{0}^{1}\ \overbrace{\int_{-\infty}^{\infty} {\pars{\expo{x}}^{\verts{k}\ic} \over \expo{2x} + 1}\,\expo{x}\,\dd x} ^{\ds{\mbox{Set}\ \expo{x} \equiv t}}\ \,\dd k =2\int_{0}^{1}\color{#00f}{% \Re\int_{0}^{\infty}{t^{\verts{k}\ic} \over t^{2} + 1}\,\dd x}\,\dd k\tag{1} \end{align}
    \begin{align}&\color{#00f}{% \Re\int_{0}^{\infty}{t^{\verts{k}\ic} \over t^{2} + 1}\,\dd x} =\Re\bracks{2\pi\ic\,{\pars{\expo{\pi\ic/2}}^{\verts{k}\ic} \over 2\ic} + 2\pi\ic\,{\pars{\expo{3\pi\ic/2}}^{\verts{k}\ic} \over -2\ic} -\int_{\infty}^{0} {t^{\verts{k}\ic}\pars{\expo{2\pi\ic}}^{\verts{k}\ic} \over t^{2} + 1}\,\dd t} \\[3mm]&=\pi\expo{-\pi\verts{k}/2} -\pi\expo{-3\pi\verts{k}/2} +\expo{-2\pi\verts{k}}\color{#00f}{% \Re\int_{0}^{\infty}{t^{\verts{k}\ic} \over t^{2} + 1}\,\dd x} \\[5mm]&\imp\ \color{#00f}{% \Re\int_{0}^{\infty}{t^{\verts{k}\ic} \over t^{2} + 1}\,\dd x} ={\pi\expo{-\pi\verts{k}/2} -\pi\expo{-3\pi\verts{k}/2} \over 1 - \expo{-2\pi\verts{k}}} =\pi\,{\expo{\pi\verts{k}/2} -\expo{-\pi\verts{k}/2} \over \expo{\pi\verts{k}} - \expo{-\pi\verts{k}}} \\[3mm]&=\pi\,{\sinh\pars{\pi\verts{k}/2} \over \sinh\pars{\pi\verts{k}}} ={\pi \over 2}\,\sech\pars{{\pi \over 2}\,k} \end{align}
    Replacing in $\pars{1}$: \begin{align} &\color{#66f}{\large\int_{-\infty }^{\infty }{\sin\pars{x} \over x\cosh\pars{x}} \,\dd x} =2\int_{0}^{1}{\pi \over 2}\,\sech\pars{{\pi \over 2}\,k}\,\dd k =\left. 4\arctan\pars{\tanh\pars{{\pi \over 4}\,k}}\right\vert_{0}^{1} \\[3mm]&=\color{#66f}{\large 4\arctan\pars{\tanh\pars{\pi \over 4}}} \approx {\tt 2.3218} \end{align} This result can be expressed in terms of the Gudermannian Function $\ds{{\rm gd}\pars{z} \equiv 2\arctan\pars{\expo{z}} - {\pi \over 2}}\quad$ as $\quad\ds{4\arctan\pars{\tanh\pars{\pi \over 4}} = 2\,{\rm gd}\pars{\pi \over 2}}$.
  2. $\ds{\large\color{#000}{\tt I_{2}\equiv \int_{-\infty }^{\infty }{\sin^{2}\pars{x} \over x\sinh\pars{x}} \,\dd x}}$
    $\tt\mbox{It can be evaluated by following a similar technique}$.

I do not know of a closed form but it seems that the integral can be converted into an infinite series. Let $$ I_{1}(k)=\int_{-\infty }^{+\infty }dx\frac{\sin kx}{x\cosh x} $$ so $I_{1}=I_{1}(1).$ Now (note that $I_{1}(0)$ vanishes) \begin{eqnarray*} \partial _{k}I_{1}(k) &=&\int_{-\infty }^{+\infty }dx\frac{\cos kx}{\cosh x}=% {Re}\int_{-\infty }^{+\infty }dx\frac{\exp [ikx]}{\cosh x}\\&=&2{Re}% \int_{-\infty }^{+\infty }dx\exp [ikx]\frac{1}{\exp [x]+\exp [-x]} \\ I_{1} &=&\int_{0}^{1}dk\partial _{k}I_{1}(k) \end{eqnarray*} If this Fourier transform is known we can try to integrate over $k$ and obtain $I_{1}(k)$ and hence $I_{1}$. If not we note that $(\exp [z]+\exp [-z])^{-1}$ has poles $z_{n}=i\pi (1+2n)$ so closing the contour in the upper half plane results in $$ \int_{-\infty }^{+\infty }dx\exp [ikx]\frac{1}{\exp [x]+\exp [-x]}=2\pi i\sum_{n}r_{n}\exp [ikz_{n}] $$ where the $r_{n}$ are the residues and the sum over $n$ is that with $z_{n}$ in the upper half plane. Now the $k$-integral can be done and we end up with a sum over $n$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.